Prevalence of asthma and asthma-like and allergic symptoms in the urban adult population of Elazığ - Tug, Tuncer; Açık, Yasemin; Tuğ, Esra (My University, 2002)
The aim of this study was to determine the prevalence of asthma, asthma-like symptoms and atopy in the adult population of the city of Elazığ. A specific questionnaire, adopted from the European Community Respiratory Health Survey including social status and smoking tendencies of people was filled in by 2454 randomly chosen (1088 male, 1366 female) subjects. The cumulative prevalence of asthma and asthma-like symptoms for males, females and the general population was 22.0%, 28.7%, and 25.7%, respectively. The periodic prevalences of them were 17.3%, 20.5%, and 19.1%, while rates of previously diagnosed asthma were 2.6%, 3.5%, and 3.1%. Subjects suffering from allergic symptoms constituted 21.0% of males, 25.5% of females and 23.6% of the total. The rates of seasonal rhinoconjunctivitis were 7.5%, 8.7%, and 8.2%, while the rates of perennial catarrh were 4.0%, 3.9%, and 3.9%, respectively. The rates of eczema were found to be 5.0% for males, 4.9% for females and 4.9% for the general population. Among the subjects suffering from wheezing and shortness of breath at any time, 11.1% had received a diagnosis of asthma previously (p<0.001). Similarly, 14.3% of subjects suffering from wheezing within the previous 12 months had been diagnosed as asthmatic (p<0.001). Our findings were parallel to those performed in different regions of Turkey. However, not all of the subjects suffering from asthma or asthma-like symptoms had been examined by chest physicians thoroughly in this study; therefore, the exact prevalence values need to be determined by large clinical studies.
Keywords: Adult; Urban Population; Hypersensitivity; Allergy and Immunology; Questionnaires; Asthma